2020
DOI: 10.1002/iroh.201902037
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of rotifers' feeding guilds shaped by chlorophyll‐a, nitrate, and environmental heterogeneity in subtropical floodplain lakes

Abstract: In floodplains, rotifers are among the most abundant zooplankton organisms and play an important role in ecosystem functioning. Here, we evaluated the distribution of six feeding guilds of rotifers including filter C1 (body size: <200 µm), filter C2 (body size: >200 to <600 µm), filter C3 (body size: >600 to <1000 µm), filter C4 (body size: >1000 µm), suctor, and predator for 11 years. We also analyzed the relationship between guild distribution and environmental parameters (i.e., chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…These distributions could be determined from published and future studies on the taxonomic structure of rotifer communities, and then used to compare rotifer communities across space or time in both natural ecosystems and outdoor, experimental mesocosms. The diet‐based, food‐niche categories proposed here are an alternative to the functional groups of planktonic rotifers that have been based on: (1) Pourriot's feeding mode dichotomy, where rotifers are considered to be either microphagous or raptorial (Smith et al 2009; Obertegger et al 2011); (2) feeding mode and body size (Bertani et al 2012; Palazzo et al 2021); or (3) the morphology of the jaws and corona (Qian et al 2022).…”
Section: Synthesismentioning
confidence: 99%
“…These distributions could be determined from published and future studies on the taxonomic structure of rotifer communities, and then used to compare rotifer communities across space or time in both natural ecosystems and outdoor, experimental mesocosms. The diet‐based, food‐niche categories proposed here are an alternative to the functional groups of planktonic rotifers that have been based on: (1) Pourriot's feeding mode dichotomy, where rotifers are considered to be either microphagous or raptorial (Smith et al 2009; Obertegger et al 2011); (2) feeding mode and body size (Bertani et al 2012; Palazzo et al 2021); or (3) the morphology of the jaws and corona (Qian et al 2022).…”
Section: Synthesismentioning
confidence: 99%
“…However, a comprehensive understanding of the linkage between environmental factors and the water trophic state is rarely reported. Environmental heterogeneity can reflect variations in environmental properties [ 25 ], and earlier studies report that water environmental heterogeneity changed temporally in the subtropical Paraná River during flooding [ 25 , 34 ]. We found that aggravated algal blooms resulted in decreased environmental heterogeneity, which has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding mode, or the method of resource acquisition, was classified according to Sommer & Stibor (2002), Branstator (2005) and Barnett et al (2007) for cladocerans; Dussart & Defaye (2001) for copepods; and Hillbricht-Ilkowska (1983) and Gilbert (2022) for rotifers. For some rotifer taxa, no published information regarding feeding mode was available; in that case, feeding mode was determined based on the morphology of the trophis (i.e., the grinding apparatus) according to Oh et al (2017) and Palazzo et al (2021). Groups with different maximum population growth rates were classified according to Allan (1976).…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 15, 2024. ; https://doi.org/10.1101/2024.04.12.589151 doi: bioRxiv preprint apparatus) according to Oh et al (2017) and Palazzo et al (2021). Groups with different maximum population growth rates were classified according to Allan (1976).…”
Section: Taxa and Trait Unitsmentioning
confidence: 99%